2000
DOI: 10.1191/096032700701546514
|View full text |Cite
|
Sign up to set email alerts
|

The composition of cigarette smoke: a retrospective, with emphasis on polycyclic components

Abstract: The difficulties encountered in extrapolating biological activity from cigarette smoke composition provide generally applicable lessons as they are representative of the problems encountered with other complex mixtures. Researchers attempting to assess risk are faced with attempting to interpret data from a number of areas including: tobacco science; smoke/aerosol chemistry specific to tobacco; sophisticated analytical chemistry applications and techniques for trapping, collecting, separating, and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(98 citation statements)
references
References 116 publications
1
97
0
Order By: Relevance
“…Comparing marijuana to tobacco, there were generally lower levels of phenolics in mainstream smoke of marijuana, although resorcinol was higher. These slight reductions may support combustion temperature differentials, although the use of pyrolysis studies on tobacco under controlled conditions for comparison to cigarette smoking has been put in question, given the complexity of the latter (8). Tables 9 and 10 present the data for PAHs and aza-arenes from marijuana and tobacco in mainstream and sidestream smoke, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing marijuana to tobacco, there were generally lower levels of phenolics in mainstream smoke of marijuana, although resorcinol was higher. These slight reductions may support combustion temperature differentials, although the use of pyrolysis studies on tobacco under controlled conditions for comparison to cigarette smoking has been put in question, given the complexity of the latter (8). Tables 9 and 10 present the data for PAHs and aza-arenes from marijuana and tobacco in mainstream and sidestream smoke, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(Johnson et al 2009), contains such chemicals, whereas cigarette smoke extract generated by bubbling cigarette smoke through culture media corresponds to only water-soluble smoke chemicals (Muller and Gebel 1998). With respect to inhibition of OATP1B1 and OCT1, a major role for PAHs, that constitute major toxic components of cigarette smoke (Rodgman et al 2000), can likely be excluded owing to the fact that both benzo(a)pyrene and phenanthrene features that determine such a cis-stimulatory effect remain however very poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the presence of compounds such as polycyclic aromatic hydrocarbons (PAH), N-nitrosamines particularly nicotine-derived nitrosamines, aromatic amines, benzene and heavy metals, which are independently established as carcinogens for humans, in the tobacco smoke (Rodgman et al, 2000;Hoffman et al, 2001;Pfeifer et al, 2002). This study found that almost all of the smoking variables studied (smoking status, type of tobacco and pack-years of exposure of tobacco) conferred an increased oral cancer risk of at least two-fold.…”
Section: Discussionmentioning
confidence: 99%